Do we need to worry about eating wheat? - Shewry, P. R. (Nutr Bull, 2016)
Wheat is a staple food throughout the temperate world and an important source of nutrients for many millions of people. However, the last few years have seen increasing concerns about adverse effects of wheat on health, particularly in North America and Europe, with the increasing adoption of wheat‐free or gluten‐free diets. This relates to two concerns: that wheat products are disproportionally responsible for increases in obesity and type 2 diabetes and that wheat gluten proteins cause a range of adverse reactions, including allergies, coeliac disease and ‘non‐coeliac gluten sensitivity’. The first concern has been refuted in previous publications, and we therefore focus on the second here. Current evidence indicates that allergy to ingested wheat and coeliac disease (and related intolerances) each occur in up to 1% of the population. The extent to which their prevalence has increased is difficult to quantify due to improved diagnosis and increased awareness. However, neither appears to be increasing disproportionally when compared with other immunologically mediated adverse reactions to food. Other adverse reactions to wheat are more difficult to define as their mechanisms are not understood and they are therefore difficult to diagnose. In particular, ‘non‐coeliac wheat sensitivity’ has been reported to occur in 6% or more of the population in the US. However, the application of more rigorous diagnostic criteria is likely to give substantially lower estimates of prevalence. It is therefore unlikely that the health of more than a small proportion of the population will be improved by eliminating wheat or gluten from the diet. In fact, the opposite may occur as wheat is an important source of protein, B vitamins, minerals and bioactive components.